KUALITAS PENTATAHAN RELIEF DI KOMPLEKS CANDI PRAMBANAN - Hari Lelono (BRIN, 1996)
Is there a relationship between the sculpting technique and the theme of the story? As is known in the Ciwa and Brahma Temples (the Ramayana story) tells the journey of a noble or king, so it requires complete accessories. On the other hand, in the Vishnu temple, Kresnayana's story tells of Kresna's